The Organizing Management of Arabic Language Program in Islamic Senior High School of West Seram, Maluku Province - Mawaddah Ahmad Opier, Ulfa; Mufidah, Nuril (12 Waiheru, 2022)
This study describes the stages of the process and the principles of implementing the Organizing Management function in the Arabic Language Program at the Islamic Senior High School of West Seram. This research uses a descriptive qualitative method. The data collection technique used is non-participant observation, in-depth interviews, and documentation. Observation of the running of the Club. Interviews were conducted by interviewing the principal, Arabic teacher, and club tutor. The analysis technique adopts the Miles and Huberman model, namely Data Reduction, Data Presentation, and Drawing Conclusions. The research showed that: (1) The Arabic club of Islamic Senior High School of West Seram applies two organizing management functions, namely determining the plans and objectives of the Arabic Club, and conducting evaluations; (2) Three principles of Organizing management have been applied in the Arabic Club, including power and responsibility by club tutors, direction and teamwork. It is known that the organizing management at the Arabic Club of Islamic Senior High School of West Seram is not well structured because there is no organizational structure and a clear division of organizational tasks.